Iron Ion Removal from Water Using Clay Honeycomb Monolith - Darmadi Darmadi; Mirna Rahmah Lubis; Adisalamun Adisalamun; Muhammad Zaki (Jurnal Kimia Sains dan Aplikasi, 2026)
Groundwater contamination by dissolved iron remains a widespread problem, particularly in decentralized water treatment systems, where simple, hydraulically efficient solutions are required. This study investigates a clay-based honeycomb monolith (CBM) as a structured adsorbent for Fe2+ removal from aqueous solutions, with simultaneous evaluation of adsorption and flow performance. The CBM was fabricated from natural clay and characterized using XRD, BET, SEM, and FTIR analyses. Batch adsorption experiments were conducted at Fe2+ concentrations of 2–9 mg L−1, and kinetic and isotherm models were applied. In addition, pressure drop measurements were performed under continuous-flow conditions using monoliths of varying heights. The CBM exhibited a specific surface area of 55 m2 g−1 and followed pseudo-second-order kinetics, while equilibrium data were best described by the Langmuir model with a maximum adsorption capacity of 0.229 mg g−1. Importantly, the monolithic structure exhibited low pressure drop (up to 18.54 kPa m−1), significantly lower than that of typical packed beds. The unique contribution of this work is to demonstrate that clay-based honeycomb monoliths can combine adsorption functionality with favorable hydraulic performance, highlighting their potential for practical iron removal in continuous-flow water treatment systems.